Geoengineering: carbon dioxide removal - Rolston, Holmes, 1932-2025, author (Colorado State University. Libraries, 2024)
A discourse about "geoengineering." Includes an anecdotal story about Dr. Rolston's grandparents.
Keywords: geoengineering; greenhouse gases; Earth systems; intervention